Literatura bazowa „ewangelii społecznej” - Drożdż, Bogusław (Społeczeństwo, 2022)
„Social Gospel” is addressed to everybody, especially Christians, clergymen, and secular Catholics. Their major common characteristic is „good will”. It is a sufficient condition to allow learning about the meaning behind the „social teachings of the Church”. Teachings of the Church state that „social education presents the basic criteria for pastoral activities within the social area: proclaiming the Gospel; confronting the evangelical message with social reality; planning activities to restore such realities through transformation according to the requirements of Christian morality” (Kompendium nauki społecznej Kościoła 526). In his social encyclical, John Paul II draws attention to the fact that „new evangelization, which the world is in urgent need of (...) must include, as one of its significant components, the proclamation of social teachings of the Church, which nowadays has been able (...) to show the just path and undertake any challenges of the modern era, while other ideologies become unreliable” (Centesimus annus 5). Benedict XVI, in his encyclical titled Caritas in veritate, noticed that social teachings of the Church are „caritas in veritate in re sociali: the proclamation of truth of Christ’s love among the society. Such teachings are the service of love, but in a true manner”.